The formulation and effect of tiger milk mushroom and cordyceps from cold extraction method for therapeutic application - Peck, En Ting (2025)
This research studied the potential therapeutic benefits of formulations made from Lignosus rhinocerus (tiger milk mushroom) and Cordyceps sinensis using the cold extraction method. The purposes of this research were to evaluate the anti-inflammatory and antioxidant properties of these formulations and identify the bioactive compounds responsible for these effects. The formulations were tested for their anti-inflammatory and antioxidant properties through BSA and casein protein assays, as well as DPPH and FRAP tests. FTIR and HPLC analyses were also conducted to identify the compounds present. Among the formulations, Formulation E (2:1 ratio of L. rhinocerus to C. sinensis) showed the best results, with 87.25% and 78.21% inhibition in the BSA and casein protein assays, respectively. It also demonstrated the highest antioxidant activity, achieving an RSA of 80.55% and a FRAP absorbance reading of 0.785 ± 0.037. FTIR detected functional groups like amines and alkenes, however, HPLC failed to identify bioactive compounds such as gallic acid and aspirin-like substances. However, HPLC was successfully identified the presence of cordycepin. The results indicated that Formulation E has the greatest potential for therapeutic use. To improve the research, it is recommended to ensure proper sterility during sample preparation and extraction. Also, include additional tests like antimicrobial and toxicity studies. Enhancing data analysis with advanced statistical methods would further improve the accuracy and reliability of the findings, supporting the development of these formulations for health or pharmaceutical applications.